面向食品药品的区块链防伪溯源方法和系统 (2025)
本发明涉及区块链技术领域，提供一种面向食品药品的区块链防伪溯源方法和系统，方法包括以下步骤：S1，在彩色图像中嵌入带有加密信息的干涉条纹，生成产品的光学加密图像；S2，将光学加密图像的相位模式与每个区块链节点的产品的哈希值动态绑定；S3，基于光学加密图像的物理特征和光学加密图像的相位模式与区块链节点的动态绑定关系，对产品进行验证。本发明解决了食品药品流通中物理标签易复制且禁用场景多、数据易篡改风险高、动态防伪能力不足及窜货检测滞后的技术问题，实现了物理特征与数字特征的双重互锁验证，确保食品药品生产流通消费全链路实时可信追溯，为食品药品行业提供了安全可靠、灵活普适的防伪追溯解决方案。 The invention relates to the technical field of block chains, and provides a food and drug-oriented block chain anti-counterfeiting traceability method and system, and the method comprises the following steps: S1, embedding interference fringes with encrypted information in a color image, and generating an optical encrypted image of a product; s2, dynamically binding the phase mode of the optically encrypted image with the hash value of the product of each block chain node; and S3, verifying the product based on the physical characteristics of the optical encryption image and the dynamic binding relationship between the phase mode of the optical encryption image and the block chain node. According to the invention, the